An improved instrument for the in vivo detection of lead in bone. Issue 7 (July 1993) - Gordon, C L; Chettle, D R; Webber, C E
Abstract : An improved instrument for the fluorescence excitation measurement of concentrations of lead in bone has been developed. This is based on a large area high purity germanium detector and a point source of 109Cd. The source is positioned in a tungsten shield at the centre of the detector face such that 88keV photons cannot enter the detector directly. In vivo measurements are calibrated with plaster of Paris phantoms. Occupationally non-exposed men show a minimum detectable concentration of about 6 micrograms/g bone mineral. Measurements of tibia lead concentrations in 30 non-occupationally exposed men between the ages of 23 and 73 showed an annual increment of 0.46 microgram/g bone mineral/year. The mean deviation from the regression of tibia lead upon age was 3.5 micrograms/g bone mineral. Tibia lead concentration in one subject with a history of exposure to lead was 69.6 (SD 3.5) micrograms/g bone mineral. The improved precision of the point source large detector system means that greater confidence can be placed on the results of in vivo measurements of lead concentration. This will allow studies of the natural history of non-occupational lead accumulation in normal subjects and should permit investigations of the efficacy of therapeutic interventions in subjects poisoned with lead.